2006
DOI: 10.1159/000093055
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Antiapoptotic Proteins Clusterin and Bcl-2 in Laryngeal Squamous Cell Carcinomas

Abstract: Bcl-2 and clusterin genes have been related to the inhibition of apoptosis, an event that plays a key role in malignant transformation and in invasive disease. In this work, we determine the significance of clusterin and bcl-2 expression in a large series of laryngeal carcinomas. We used immunohistochemical methods and in situ hybridization to examine the expression of these proteins. Nontumoral epithelial laryngeal tissues did not express clusterin and bcl-2 proteins. However, 9% (14 out of 154) and 25% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
(28 reference statements)
3
14
0
3
Order By: Relevance
“…Recently, many reports have indicated that ectopic expression of Bcl-2 attenuates anticancer agents to illicit an apoptotic response through a caspase cascade [30,31]. Our data showed that BV treatment results in a progressive expansion of apoptotic population at 48 h and decreased expression of the Bcl-2 protein.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, many reports have indicated that ectopic expression of Bcl-2 attenuates anticancer agents to illicit an apoptotic response through a caspase cascade [30,31]. Our data showed that BV treatment results in a progressive expansion of apoptotic population at 48 h and decreased expression of the Bcl-2 protein.…”
Section: Discussionsupporting
confidence: 57%
“…sCLU overexpression reaches a maximum at three to four days post-castration and coincides with the onset of massive cell death [3]. The sCLU level also rises in various malignant tumors, including gastric cancer [4], ovarian cancer [5], breast cancer [6], bladder cancer [7], colorectal cancer [8], hepatocellular carcinoma [9], prostate cancer [10] and laryngeal squamous cell carcinomas [11]. In these cancers, sCLU overexpression has been reported to be closely associated with cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study found sCLU was overexpressed in laryngeal carcinomas, and clusterin expression was significantly related to the degree of local invasion [11]. However, whether sCLU may be a target for the treatment of laryngeal carcinomas has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to verify this association, further studies in larger series of pituitary adenomas are required. Increased clusterin levels were reported in various neoplasms such as colonic adenomas and carcinomas, hepatocellular carcinomas, ovarian carcinomas, urothelial carcinomas, and laryngeal carcinomas as well [12,13,16,18,23]. However, clusterin localization in pituitary adenomas was not reported previously.…”
Section: Discussionmentioning
confidence: 91%
“…Upregulation of clusterin was found correlated with aggressive behavior and decreased survival in some neoplasms [12,13,16,18,19,23]. Several authors have proposed that the anti-apoptotic activity of clusterin may account in part for the genesis and biologically aggressive behavior of some types of tumor cells [17,18]. Clusterin has been involved in apoptosis as a proapoptotic or antiapoptotic molecule in a variety of models and under distinct experimental conditions [21].…”
Section: Discussionmentioning
confidence: 99%